Utilization of Neuromuscular Electrical Stimulation as a Rehabilitation Treatment in Heart Failure with Reduced Ejection Fraction: A Systematic Review and Meta-Analysis - Bima Diokta Alparisi; Samira Amanda; Daniel Herman; Rosmaliana Rosmaliana; Irwan Irwan; Haryadi Haryadi (The Indonesian Heart Association, 2026)
Heart Failure with Reduced Ejection Fraction (HFrEF) is associated with substantial functional impairment, and many patients are unable to participate in conventional exercise-based cardiac rehabilitation. Neuromuscular Electrical Stimulation (NMES) has been proposed as an alternative rehabilitation treatment, but its clinical effectiveness remains uncertain. This review aims to evaluate the effectiveness of NMES in improving cardiac function and exercise capacity in patients with HFrEF. A systematic review and meta-analysis of Randomized Controlled Trials (RCTs) was conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Studies comparing NMES with standard medical therapy, exercise training, or no intervention in adult patients with HFrEF were identified through major electronic databases. Risk of bias was assessed using the Cochrane RoB 2.0 tool. Pooled effects were calculated as Mean Differences (MD) with 95% Confidence Intervals (CIs) using Review Manager (RevMan) version 5.4. Twelve RCTs involving 636 participants were included. NMES significantly improved peak oxygen uptake (VO2 peak) (MD 2.03 mL/kg/min; 95% CI 1.21 to 2.84; p < 0.00001), systolic blood pressure (MD −2.02; 95% CI −3.97 to −0.06; p = 0.04), Left Ventricular Ejection Fraction (LVEF) (MD −1.38%; 95% CI −2.73 to −0.03; p = 0.05), and Heart Rate (HR) (MD 2.19 beats/min; 95% CI 0.44 to 3.95; p = 0.01). A borderline significant improvement was observed in the Six-Minute Walk Test (6MWT) distance (MD −11.40 m; 95% CI −23.04 to 0.24; p = 0.05). No significant effects were found for diastolic blood pressure (MD −0.12; 95% CI −3.30 to 3.06; p = 0.94) or Minnesota Living with Heart Failure Questionnaire (MLHFQ) scores (MD 1.97; 95% CI −9.06 to 13.01; p = 0.73). NMES is associated with meaningful improvements in exercise capacity and selected parameters of cardiac function in patients with HFrEF, supporting its role as a potential adjunct rehabilitation treatment.